The Integration of Religious Moderation Values in Islamic Religious Education Learning at Public Universities (Efforts and Constraints in the Implementation of Anti-Radicalism Education) - Herlinawati, Herlinawati (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The development of radical understandings and attitudes that also penetrate the campus world that needs to be addressed by including religious moderation and understanding of Islamic Religious Education (IRE) learning in Public Universities in the framework of implementing anti-radicalism education in IRE learning in Public Universities. This study aims to see the integration of moderation values in IRE learning in public universities in the application of anti-radicalism education, as well as what alarms are the obstacles. The approach used in this study is a descriptive qualitative approach, with the analysis stages in the form of data reduction, data presentation and conclusion drawing. The results showed that first, the values of religious moderation have been integrated in the learning of IRE in Public Universities through materials related to tolerance, brotherhood (ukhuwah), and the concept of Islamic teachings as a religion of rahmatan lil 'alamin. Second, the implementation of anti-radicalism education in IRE learning at public universities is seen from the content of the Semester Learning Plan (SLP) and Subject Learning Outcomes (SLO), most of the respondents have formulated it, only a small part is not specifically. There are several relationships that exist in the implementation of anti-radicalism education related to reference materials, time, and learning media.